2019
DOI: 10.1002/celc.201901208
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Electrochemical Properties of LiNi0.8Co0.1Mn0.1O2 Cathode Materials Modified with Lithium‐Ion Conductive Coating LiNbO3

Abstract: As a promising cathode material for lithium‐ion batteries, nitrogen‐rich LiNi0.8Co0.1Mn0.1O2 (NCM811) attracts great attention for its high specific capacity, but the rapid capacity decline of NCM811 in the process of charge/discharge restricts its extensive application. To alleviate the capacity decline for NCM811, a solid electrolyte LiNbO3 material with lithium‐ion diffusion and electron conduction activity was successfully coated on the surface of NCM811 by adopting a simple two‐step method, and the amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Selected fast Fourier transform (FFT) patterns of the region I confirm the formation of a typical layered structure, consistent with previous reports. 24,25 For NCM90 cycled in BE, two more phases can be identified from Fig. 2(a), an amorphous phase layer with a width of ~3.2 nm forms near the interface, (from the blue dotted line to the surface), followed by a double-layer structure of rock salt phase (~8.1 nm, between red and blue dotted line) between the amorphous layer and the bulk region.…”
Section: Resultsmentioning
confidence: 99%
“…Selected fast Fourier transform (FFT) patterns of the region I confirm the formation of a typical layered structure, consistent with previous reports. 24,25 For NCM90 cycled in BE, two more phases can be identified from Fig. 2(a), an amorphous phase layer with a width of ~3.2 nm forms near the interface, (from the blue dotted line to the surface), followed by a double-layer structure of rock salt phase (~8.1 nm, between red and blue dotted line) between the amorphous layer and the bulk region.…”
Section: Resultsmentioning
confidence: 99%
“…Whether LiNbO 3 coating layer is crystalline or amorphous is almost affected by the synthetic methods and heat treatment temperature in the preparation process. [90][91][92][93][94][95][96] Highly crystalline LiNbO 3 coating can be obtained by solid-state reaction method or heat treatment at higher temperature based on the solution method. [97][98][99] However, compared to crystalline LiNbO 3 , amorphous LiNbO 3 coating not only can deform elastically to avoid cracking during strain generation due to lower stiffness, but also has higher ionic conductivity, which makes CAMs with amorphous LiNbO 3 coating present better electrochemical performance.…”
Section: Lithium Metallic Oxide Active Coating Layermentioning
confidence: 99%
“…In order to solve the above problems, many studies have reported the method of interfacial coating. [ 159–165 ] A reasonable design of the interface coating can reduce the electronic conduction and interface resistance between the SSE and the electrode while providing a physical barrier to prevent the occurrence of side reactions, such as Li plating, at the interface. Han et al [ 138 ] used ALD method to deposit Al 2 O 3 on garnet‐type Li 7 La 2.75 Ca 0.25 Zr 1.75 Nb 0.25 O 12 (LLCZN), which significantly improved the wettability and stability of the interface between the SSE and lithium metal.…”
Section: Battery Structure Design For Fast‐chargingmentioning
confidence: 99%